The Intervention of Physiotherapy in the improvement of facial mimicry in a Peripheral Facial Palsy associated with a Pregnancy: A Case Report - Felício, João Carlos Martins (Brazilian Journal of Case Reports, 2023)
Peripheral Facial Palsy is a peripheral paralysis of the facial nerve that results in muscle weakness on one side of the face. Patients develop unilateral facial paralysis within one to three days with involvement of the facial musculature associated or not with neurological alterations, the best-known being Bell’s Palsy. Symptoms usually peak in the first week and then gradually subside over three weeks to three months. In this context, a female patient with the clinical Diagnosis of Peripheral Facial Paralysis, was subjected to an intervention plan in Physiotherapy lasting 4 months (sessions of 45 minutes at a frequency of 3 times a week), with the particularity of be 28 weeks pregnant at the start of the sessions. After the end of the sessions, there was a considerable improvement in facial movements, translating into considerable functional changes. The patient acquired greater motor recruitment in flaccid muscles, greater facial symmetry, and consequently greater autonomy in eating, chewing, containing liquids and intraoral sensibility.